2023
DOI: 10.52312/jdrs.2024.975
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model for osteonecrosis of femoral head after internal fixation with multiple cannulated compression screws for adult femoral neck fractures

Zhang Jin,
Luo Chen,
Dafeng Wang
et al.

Abstract: Objectives This study aims to investigate the high-risk factors for osteonecrosis of the femoral head (ONFH) after internal fixation with multiple cannulated compression screws for adult femoral neck fractures and to construct a prediction model. Patients and methods Between from January 2012 and December 2020, a total of 268 patients (138 males, 130 females; mean age: 53±10 years; range, 23 to 70 years) with ONFH who had complete follow-up data were included. Closed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Some hypotheses suggested that this would lead to or exacerbate aseptic necrosis of the femoral neck and head. Jin established a predictive model for femoral head necrosis following femoral neck fracture surgery, with data indicating that removal of internal fixation is an independent risk factor [ 7 ]. Some scholars [ 8 ] speculated that the presence of internal fixation increased pressure within the femoral head, exacerbating damage to the femur.…”
Section: Introductionmentioning
confidence: 99%
“…Some hypotheses suggested that this would lead to or exacerbate aseptic necrosis of the femoral neck and head. Jin established a predictive model for femoral head necrosis following femoral neck fracture surgery, with data indicating that removal of internal fixation is an independent risk factor [ 7 ]. Some scholars [ 8 ] speculated that the presence of internal fixation increased pressure within the femoral head, exacerbating damage to the femur.…”
Section: Introductionmentioning
confidence: 99%